2021
DOI: 10.1101/2021.08.09.21261277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of regional lockdown policies on COVID-19 transmission in India in 2020

Abstract: Objective: To assess the impact of non-pharmaceutical interventions (NPIs) on the first wave of COVID transmission and fatalities in India. Methods: We collected data on NPIs, using government notifications and news reports, in six major Indian states from March to August 2020, and we matched these with district-level data on COVID related deaths and Google Mobility reports. We used a district fixed effect regression approach to measure the extent to which district-level lockdowns and mobility restrictions he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Bihar, Karnataka, Andhra Pradesh, and Tamil Nadu observed an increase in death rate in the post-lockdown phases 27 , similar to our findings that showed an increase in death rates during the same period. By simple regression analysis, Goshal et al found that there was a 45% reduction in total infection in India after one week from the declaration of the lockdown which conforms to our findings of case growth that slowly declined throughout the lockdown phases 28 .…”
Section: Discussionsupporting
confidence: 92%
“…Bihar, Karnataka, Andhra Pradesh, and Tamil Nadu observed an increase in death rate in the post-lockdown phases 27 , similar to our findings that showed an increase in death rates during the same period. By simple regression analysis, Goshal et al found that there was a 45% reduction in total infection in India after one week from the declaration of the lockdown which conforms to our findings of case growth that slowly declined throughout the lockdown phases 28 .…”
Section: Discussionsupporting
confidence: 92%